Gender differences in ADHD and impulsivity among alcohol or alcohol- and cocaine-dependent patients - Roncero, Carlos; Remón-Gallo, Diego; García-Ullán, LLanyra; Vicente-Hernández, Begoña; Buch-Vicente, Barbara; Palma-Álvarez, Raul Felipe; Grau-López, Lara; González-Bolaños, Kristofer Ramon; Álvarez-Navares, Ana; Pérez, Jésus; Aguilar, Lourdes (Frontiers in Psychiatry, 2025)
BackgroundImpulsivity plays a fundamental role in the realm of addiction as is considered a risk factor for addiction. Moreover, it influences the age of onset, severity, and therapeutic management of addictions. The aim of this study was to explore measures of impulsivity in a cohort of male and female diagnosed with Alcohol Use Disorder (AUD) and contrast these findings with those from a group with Alcohol and Cocaine Use Disorder (ACUD).MethodologyA total of 204 patients (153 men and 51 women) underwent evaluation using Adult ADHD Self-Report Scale (ASRS), Barrat Impulsiveness Scale (BIS-11), Zuckerman-Kuhlman Personality Questionnaire (ZKPQ), Visual Analogue Scale (VAS), Beck Depression Inventory (BDI) and State-Trait Anxiety Inventory (STAI).ResultsA total of 24.6% of the sample (21.9% AUD group and 32.2% ACUD group) screened positive for ADHD. Differences were observed in Total Impulsivity (T(199) =-2.587, p=.010), with the mean score being higher in the ACUD group. Gender differences were noted with ADHD exhibiting a significant explanatory power for impulsivity (greater than 37%) in women compared to men, where its relevance is minimal. Among women, an inverse relationship was found between impulsivity and activity and sociability, in contrast to men, where the inverse relationship was with intolerance to isolation. Both men and women showed associations between ADHD and elevated levels of anxiety and depression. Study limitations and practical implications are discussed.ConclusionsAlthough this is an observational study and should be develop a longitudinal study, we detected that the presence of ADHD in addicted women significantly influences impulsivity and should be systematically assessed due to the differences in the clinical approach.